Treatment modalities of palmoplantar lichen planus: a brief review - Feily, Amir; Yaghoobi, Reza; Nilforoushzadeh, Mohammad Ali (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Palmoplantar lichen planus is a localized and uncommon variant of lichen planus which is mostly resistant to treatment. Our purpose was to discuss all treatment modalities proposed and tested for palmoplantar lichen planus in the literature. A systematic review of the literature was conducted to evaluate evidence regarding all treatment modalities proposed and tested for palmoplantar lichen planus in the literature. Two major databases (PubMed, Google scholar) were searched. The review included all case reports, letters and original articles reporting any treatment for palmoplantar lichen planus but not treatment used in the other type of lichen planus, generalized lichen planus or other type of palmoplantar dermatoses. We have gone over more than 50 articles. There are many drugs that have been used in the treatment of lichen planus and generalized lichen planus but the palmoplantar type is a rare variety of lichen planus. That is why we could not find any clinical trial on the subject and just case reports have been described in this manuscript. In spite of plentiful investigations carried out on lichen planus, there is no treatment modality that has proved to be utterly satisfactory in treatment of palmoplantar lichen planus.